Spatial-temporal characteristics and influencing factors of NO2 and SO2 in the Beijing-Tianjin-Hebei region based on satellite remote sensing. Issue 1 (March 2021) - Zhai, Haoran; Yao, Jiaqi; Qi, Jianwei; Wang, Guanghui; Zhang, Tao
Abstract: Air is an indispensable natural resource for all human activities. As an essential trace gas in the atmosphere, high NO2 and SO2 will affect the natural environment and human health. Based on the Ozone Monitoring Instrument's data, the temporal and spatial distribution of NO2 and SO2 concentrations in the Beijing-Tianjin-Hebei region from 2005 to 2017 was analyzed. Results showed that, on the annual scale, the concentration increased at first and then decreased. On the monthly scale, both of the two had regular fluctuations with annual cycles. The spatial distribution of pollutants was high in the southeast and low in the northwest. By analyzing the influencing factors of pollutants, it was found that environmental conditions are more the periodic fluctuations and spatial distribution differences of image density, and policy-oriented conditions are the main reason for the concentration trend decline in the later period.